2012
DOI: 10.3757/jser.71.61
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Equilibrium Examination on Stabilometry (Foulage test)^|^mdash;Physiological Character of Normal Subjects^|^mdash;

Abstract: This report is a preparatory study for a new dynamic equilibrium examination, the "Foulage test". Subjects step on the center of a stabilometer, keeping both toes constantly in contact with the plate, and lifting up only the heels alternately. Subjects had to accurately keep up a tempo of 120 beats per minute (BPM 120) as set by an electric metronome. The examination time was 60 seconds, 120 steps, with eyes open and closed.Sixteen healthy volunteers (8 men, 8 women, 24 to 55 years old, mean 36 years old) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Demura et al (2001) reported significant and high relationships among postural sway variables regarding distance, area, and speed (above 0.90). Yasuda et al (2012) reported high correlations among sway variables during stipulated tempo stepping (r 2 = 0.88). Stepping with the 40 bpm tempo has a long sway distance due to the long supporting time of a single leg, leading to a large sway area, whereas stepping with the 120 bpm tempo has a short sway distance due to the short supporting time, leading to a small sway area.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Demura et al (2001) reported significant and high relationships among postural sway variables regarding distance, area, and speed (above 0.90). Yasuda et al (2012) reported high correlations among sway variables during stipulated tempo stepping (r 2 = 0.88). Stepping with the 40 bpm tempo has a long sway distance due to the long supporting time of a single leg, leading to a large sway area, whereas stepping with the 120 bpm tempo has a short sway distance due to the short supporting time, leading to a small sway area.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, relationships among postural sway variables during static standing (Demura et al, 2001) or their fluctuations during static standing with eyes open or closed (Smith et al, 2012;Apthorp et al, 2014;Walters-Stewart et al, 2018) have been examined. Yasuda et al (2012) examined their relationships during stepping with the 120 bpm tempo and reported that high relationships are found. Uchida and Nagura (2014) examined their relationships when ascending/descending steps and while one-leg standing.…”
Section: Introductionmentioning
confidence: 99%